Social Protest and Freedom of Transit: the Costa Rican State Against the Social Movement of 2018 - Ramos Torres, Yeimer (2022)
The essay discusses, from a sociocritical perspective, the conceptual, theoretical and doctrinal elements about the functions, roles and responsibilities of the Costa Rican State, as guarantor of the legal effectiveness of the constitutional rights to social protest and freedom of transit, in the context of the mobilizations against the so-called "Fiscal Combo" of the year 2018 in Costa Rica. A bibliographic review was carried out about the main doctrinal references in relation to social protest, as well as international regulations and the Political Constitution of Costa Rica. The Doctrine of the Social Forum and the Doctrine of the Collision or Convergence of Fundamental Rights are discussed as elements of jurisprudential analysis and institutional action of the State at the time of reconciling and guaranteeing the legal effectiveness of the fundamental rights that converge in the scenario of social protests. This in order to determine the conceptual, theoretical and doctrinal background that regulate the exercise of constitutional rights to social protest and freedom of movement in Costa Rica.